A lifetime distribution motivated by parallel and series structures. Issue 13 (3rd July 2018) - Goldoust, M.; Rezaei, S.; Si, Y.; Nadarajah, S.
ABSTRACT: A new three-parameter distribution with decreasing, increasing, and bathtub-shaped hazard rates obtained by compounding geometric, power series, and exponential distributions is introduced. It includes some well-known distributions as particular cases. Various mathematical properties of the new distribution as well as details of the maximum likelihood estimation and a sensitivity analysis for its parameters are presented. Finally, two real data applications are presented.